Congenital heart disease and pregnancy - Acho Mego, Segundo (2015)
Heart disease during pregnancy is the most common non-obstetric cause of maternal death. Current increase in mothers with congenital heart disease and decline in rheumatic heart disease carriers is noted due to reduction and control of rheumatic fever and advances in medical and surgical treatment of congenital heart disease;these girls reach reproductive age. This review highlights congenital heart disease diagnosis and treatment that requires multidisciplinary approach and management in order to obtain adequate maternal-perinatal outcomes.